The Influence of Work Experience, Leadership Style, Work Environment, and Work-Life Balance on the Job Satisfaction - Khikmah, Alfiatun; Widhiandono, Hengky (Ilomata International Journal of Management, 2024)
Job satisfaction of the Purwokerto Pratama Tax Service Office (KPP) employees is an important aspect so that employees feel comfortable with their work and so that tax services can be distributed well to the community. The aim of this research is to determine the influence of work experience, leadership style, work environment, and work-life balance on employee job satisfaction. This research focuses on all civil servants (PNS) of the Purwokerto Pratama Tax Service Office (KPP), which totals 80 employees. The analysis tool used is Partial Least Squares Structural Equantum Modeling (SEM-PLS) version 4. This study employs a quantitative approach using a questionnaire with a saturated sample technique, or total sample. The research results show that work experience, leadership style, work environment, and work-life balance have a positive effect on employee job satisfaction.